The United States and Turkey: A Model of Sustained Engagement - Pearson, W. Robert (Tufts Archival Research Center, 2005)
Volume 26, Issue 1. Winter/Spring The United States could have no better ally than Turkey in its war on terrorism, writes the U.S. Ambassador to Turkey. Facing a range of economic and political challenges, Turkey now needs the United Statesï¿½ sustained engagement.